Uncovering the (possible) relationship between Central Bank Independence and economic growth in the context of monetary unions - Martins, L. F.; Clemente-Casinhas, L.; Ferreira-Lopes, A. (CESifo Economic Studies, 2024)
This work estimates the relationship between Central Bank Independence (CBI) and economic growth in the context of monetary unions, using dynamic panel models. We use two measures of CBI: the Legal CBI index and the irregular turnover rate. When an irregular turnover of the Central Bank Governor occurs, it harms growth for countries outside monetary unions. On the contrary, the Legal CBI index is a positive factor for growth, although only regarding countries belonging to monetary unions. The limitations on lending to the government is the most important component of the Legal CBI, which explains this result. Additionally, we analyse sub-samples taking into account the level of income, the number of crises, the existence of quantitative easing policies, and different time windows. Interestingly, 1990–2013 was a harmful period for growth for the entire sample but benign for countries that belong to monetary unions. Moreover, when countries are in a crisis they benefit from being a member of a monetary union with an independent central bank. Results seem to point to the conclusion that Legal CBI in a monetary union has the potential to increase economic growth rates.